On a Russian Theme in Galician Poetry: Ramón Cabanillas & Nikolay Nekrasov - Zernova, Elena (Madrygal. Revista de Estudios Gallegos, 2019)
The study analyzed a specific episode of the reception of Russian literature in Galicia linked to the name of the Galician writer Ramón Cabanillas, who in 1924 published in the newspaper A Nosa Terra an original paraphrase of the poem by Nikolai Nekrasov “The forgotten village”. Interpreting the text of Nekrasov through his own artistic vision and using a different poetic form, Cabanillas actually created a new artwork, although based on the key idea of the original. The study shed light on the reasons why the interest in oeuvre of the outstanding Russian writer emerged and on the possible ways to get acquainted with his poem. The comparative philological analysis of the Russian and Galician texts of the poem, as well as the examination of their translations into French (Alexandre Dumas) and Spanish (Antonio Balbin de Unquera), which could serve as a possible source for the Cabanillas’ version, allowed us to state that Russian literature acquired an original, sometimes unusual, reflection in the mirror of Galician culture. This fact still requires a detailed study.
Keywords: Galician Literature; Poetic Translation; Comparative Analysis; Ramón Cabanillas; Nikolái Nekrasov